Effects of preincubation of primary monolayer cultures of rat hepatocytes with low- and high-density lipoproteins on the subsequent binding and metabolism of human low-density lipoprotein. - Salter, A M (1987)
1. There are two distinct binding sites (Site 1 and Site 2) for human low-density lipoprotein (LDL) on rat hepatocytes in monolayer culture [Salter, Saxton & Brindley (1986) Biochem. J. 240, 549-557]. 2. Binding of 125I-LDL to Site 1, but not to Site 2, is up-regulated between 20 and 44 h in culture by preincubation of the cells with human high-density lipoprotein 3 (HDL3). 3. A similar preincubation with HDL2 had no significant effect on binding to either site. 4. Preincubation with human LDL led to a partial down-regulation of subsequent binding of 125I-LDL to Site 1. Since binding after incubation with LDL was measured at 37 degrees C, binding to Site 2 could not be distinguished from LDL that had been internalized by the cells. 5. Hepatocytes were shown to degrade 125I-LDL, resulting in the accumulation of [125I]iodotyrosine in the medium. Evidence was found that iodotyrosine may be further degraded by deiodinase produced by the cells. 6. Regulation of binding to Site 1 by preincubation with LDL or HDL3 was found to lead to a parallel regulation of LDL degradation. 7. It is concluded that rat hepatocytes not only bind but also metabolize human LDL and that these processes are under metabolic regulation.